2019
DOI: 10.1155/2019/9570616
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products: Potential Mechanism and Therapeutic Target in Cardiovascular Complications under Diabetes

Abstract: The occurrence and development of cardiovascular complications are predominantly responsible for the increased morbidity and mortality observed in patients with diabetes. Oxidative stress under hyperglycemia is currently considered the initial link to diabetic cardiovascular complications and a key node for the prevention and treatment of diabetes-related fatal cardiovascular events. Numerous studies have indicated that the common upstream pathway in the context of oxidative stress in the cardiovascular system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 139 publications
(141 reference statements)
0
74
0
14
Order By: Relevance
“…Since they are highly reactive and potent, glycating agents can generate more AGEs by reacting with proteins, in turn [98]. It was shown that AGE accumulation causes inflammation and destroys the normal structure and function of blood vessels, leading to vascular complications [101]. AGEs can also act by bonding to RAGEs (receptor for advanced glycation end-products) in plasma membrane and this interaction triggers different signaling pathways involved in apoptosis, inflammation, angiogenesis, and vasopermeability [102].…”
Section: Vitamin B6 and Diabetes Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since they are highly reactive and potent, glycating agents can generate more AGEs by reacting with proteins, in turn [98]. It was shown that AGE accumulation causes inflammation and destroys the normal structure and function of blood vessels, leading to vascular complications [101]. AGEs can also act by bonding to RAGEs (receptor for advanced glycation end-products) in plasma membrane and this interaction triggers different signaling pathways involved in apoptosis, inflammation, angiogenesis, and vasopermeability [102].…”
Section: Vitamin B6 and Diabetes Complicationsmentioning
confidence: 99%
“…Furthermore, AGEs increase the production of reactive oxygen species (ROS), which impact genome integrity [103,104]. The increase in ROS production can, in turn, promote the production of more AGEs, thereby forming a vicious circle [101].…”
Section: Vitamin B6 and Diabetes Complicationsmentioning
confidence: 99%
“…Hyperglycemia induces the production of reactive oxygen species (ROS) and AGE [19]. These products can cause oxidative stress leading to abnormal bone homeostasis [20]. Osteoblast, the bone-forming cells were inhibited and osteoclast stimulated by AGEs, causing increased bone turnover [21].…”
Section: Review Osteoporotic Fractures and Diabetesmentioning
confidence: 99%
“…As a regulator of metabolic activity, many researchers started to appreciate the role of AMPK and tried to target this pathway as a treatment of many metabolic diseases such as DM and OS. Many substances have been shown to have activity on AMPK [16,20,38,42]. Among them, MF, which is already being used as a first-line medication for DM, shows a positive regulation effect of AMPK [37,[42][43].…”
Section: Ampk=amp Activated Protein Kinase; Amp=adenosine Monophosphatementioning
confidence: 99%
“…В развитии ХСН при СД2 ключевую стимулирующую роль отводят присущим диабету изменениям, включая инсулинорезистентность, гиперинсулинемию, гипергликемию и накопление конечных продуктов гликозилирования (КПГ) -advanced glycation end-products -AGEs [2,11]. Воздействие этих факторов определяет формирование трех основных патофизиологических механизмов:…”
Section: патофизиологические аспекты развития хсн у больных с сд2unclassified